Makna Cinta Sempurna (Consummate Love) dalam Lirik dan Visual Pada Video Klip “Asmalibrasi” Karya Soegi Bornean - Yohanis, Erika; Dwivayani, Kadek Dristiana (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
"Asmalibration" is a song from the music group Soegi Bornean that has been released since 2019. In 2022, this song became popular on social media, especially TikTok and Instagram. After becoming popular, this song also became a debate on social media because the lyrics are difficult to understand. After all, it uses diction that is less known to the public. The purpose of this research is to find out the meaning of the components of love, namely intimacy, passion and commitment, and the types of love relationships contained in the lyrics and visuals in the video clip "Asmalibrasi" by Soegi Bornean. This research uses descriptive qualitative research with Ferdinand de Saussure's semiotic approach and Robert J Sternberg's love triangle theory as the supporting theory. The results showed that in the lyrics and visuals of the video clip, there are meanings in the components of intimacy, passion, and commitment and the type of love relationship that exists in the lyrics and visuals of Soegi Bornean's "Asmalibrasi" video clip is Consummate Love.